EKSPRESI WAJAH POTRET DIRI SEBAGAI SUMBER IDE PENCIPTAAN SENI LUKIS - Artayasa, I Made Ariawan Mahendra; Budiarta, Dewa Putu Gede; Yugus, A.A Gde (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2024)
The face is a representation and the identity of a person's individual. Facial expressions in social life serve as one of the mediums of communication. Various facial expressions of mutual significance can be listed as signs. Visualizing the face with its expressions (signs) into the art of painting is interesting. Real facial expressions are expressive while facial expressions in painting can contain a metaphor that can mean more than can be seen. The realization of ideas to the art of painting constitutes a phenomenon that occurs in people's lives and personal lives, while it conveys a message asa critical power that one hopes to grasp its meaning through the process of aesthetic and practical experience many benefits obtained for future reference and basis Alluding to the theme raised, it will be describred word by word with several studies of sources to avoid confusion about the meaning contained in the meanin of the title that the author has adopted so that works such as Just Fanny”, Reflecting”, Focus”, Upset”, Shame”, and Scared”. In the embodiment of the work, the sepia color is more prominent. By combining contrasting colors to produce works that become the identitiy of the ceator. In the end, the work related to the title that was appointed, namely Self-Potrait Facial Ekspressions as a Source of Painting Creator Ideas” is expected to be useful and become a shared learning.